Application Analysis of Multidisciplinary Diagnosis and Treatment Nursing Mode Based on Doctor-Nurse-Integration for Stroke Patients Undergoing Emergency Intervention Surgery. (11th November 2022) - Zhong, Hai; Liang, Aiqun; Luo, Huanhuan; Hu, Xiaolong; Xu, Shengxiang; Zheng, Ziming; Zhu, Xiaoping
Abstract : Purpose . To analyze the application value of multidisciplinary diagnosis and treatment (MDT) nursing mode based on doctor-nurse-integration for stroke patients undergoing emergency intervention surgery. Methods . In this study, a historical comparative study method was adopted. 118 stroke patients and medical staff (9 doctors and 11 nurses) who met the diagnosis and inclusion criteria of emergency intervention surgery admitted from July 2021 to February 2022 were treated clinically according to the traditional medical care mode (TMC group), 87 stroke patients and medical staff (9 doctors and 11 nurses) who met the diagnosis and inclusion criteria of emergency intervention surgery admitted from February 2022 to June 2022 were treated and cared according to the MDT nursing mode based on medical integration (MDT group). Comparison of perioperative time indicators, postoperative outcome indicators, treatment compliance, secondary complications and visit satisfaction between the two groups of patients, and comparison of cooperation satisfaction between the two groups of medical staff. Results . The MDT group had shorter onset—emergency physician's reception time, arrival at CT room—completion time of CT/MR, notify intervention chamber—arrival time at catheter chamber, admission—femoral artery puncture time, admission—first vessel recanalization time, mean postural restraint time than the TMC group (P < 0.05 ). The postoperative mortality rate in the MDT group (5.75%) was comparable to that in the TMC group (8.47%) (P > 0.05 ); the postoperative disability rate in the MDT group (28.74%) was less than that in the TMC group (45.76%) (P < 0.05 ); the NIHSS score in the MDT group was lower than that in the TMC group, and the FMA score and BI score were both higher than those in the TMC group (P < 0.05 ). The MDT group had higher treatment compliance than the TMC group, fewer secondary complications than the TMC group, and higher patient visit satisfaction and medical staff cooperation satisfaction than the TMC group (P < 0.05 ). Conclusion . The implementation of the MDT nursing mode based on the doctor-nurse-integration for stroke patients undergoing emergency intervention surgery can improve the work efficiency of rescuing patients, improve the clinical treatment outcome of patients, and improve the satisfaction of doctors, nurses, and patients.